1994
DOI: 10.1111/j.1699-0463.1994.tb05233.x
|View full text |Cite
|
Sign up to set email alerts
|

Early entry of plasma proteins into damaged neurons in brain infarcts

Abstract: Entry of plasma proteins into damaged neurons has previously been demonstrated in various pathological conditions, but little is known about brain infarcts in this respect. In the present study, focal ischemic lesions were produced in rats by permanent occlusion of the middle cerebral artery (MCA). The animals were killed from 1 to 48 h postlesion. Leakage of plasma proteins across the blood‐brain barrier into the infarcted area was visualized with immunostaining 2–3 h after the occlusion. This is earlier than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Also, significant cell injury or death could not account for epileptogenesis (Fig. 7), although it has been previously shown that vasogenic edema may be associated with accumulation of serum proteins in the cytoplasm of injured neurons (Loberg et al, 1994), followed by cytochrome release and DNA fragmentation (Matz et al, 2001). Although cell loss was not found, we show here robust enhanced GFAP staining restricted to the BBB-disrupted cortex.…”
Section: Discussioncontrasting
confidence: 51%
“…Also, significant cell injury or death could not account for epileptogenesis (Fig. 7), although it has been previously shown that vasogenic edema may be associated with accumulation of serum proteins in the cytoplasm of injured neurons (Loberg et al, 1994), followed by cytochrome release and DNA fragmentation (Matz et al, 2001). Although cell loss was not found, we show here robust enhanced GFAP staining restricted to the BBB-disrupted cortex.…”
Section: Discussioncontrasting
confidence: 51%
“…The wide inter‐individual and interregional variability in the pattern of staining is consistent with this concept, since not only the distribution, but also the specific form of tissue damage could be expected to diverge widely among individuals and regions as the brain dies. Loberg and Torvik have shown in experimental animals that serum protein uptake in damaged neuronal perikarya takes place within minutes of leakage across the blood‐brain barrier, 22 and a similar pattern can be induced by ischemia 39 . Several other serum proteins—IgG, complement C3c—are found in the brain rarely and inconsistently.…”
Section: Discussionmentioning
confidence: 99%
“…We assigned a maximal score of 16 (cortical gray matter: 4.0; cortical white matter: 4.0; hippocampus: 4.0; cerebellum: 4.0) to experimental piglets that could not survive for 5 days due to severe seizures. This was because the minimum time for visible histologic damage to develop is shorter with increasing injury severity, and an increasing number of damaged neurons are visible from 6 to 24 h (Brierley et al, 1971;Løberg et al, 1994). Early evaluation might therefore cause underestimation of the damage.…”
Section: Histologymentioning
confidence: 99%